Working for Ford forty years on - Paul K. Edwards (University of Birmingham, Birmingham Business School, 2014)
Huw Beynon's Working for Ford achieved celebrity when published in 1973. An assessment 40 years later identifies the lasting value of the book. Though written from a clearly stated point of view, it did not present a biased account, and it included much information permitting alternative assessments. It is also possible to construct an explanation of why the situation was as it was; this explanation turns on the technology of car plants, distinctive strategies adopted by Ford management, and the active role of workers. Though the particular events analysed in the book were of their time, the book is of more than historical interest. Its lasting value is four-fold: it explains how and why workers engage in immediate battles for control of the workplace; it indicates that workers do not choose such battles willingly and are often aware of wider concerns while lacking the means to pursue them; it points to substantial areas of continuity with the contemporary organization of labour and struggles for workers' dignity; and it permits reflection on the possibilities of organized alternatives to current forms of work organization.
Keywords: 330; Beynon; car industry; Ford; social class; sociology of work; workplace industrial relations